Needs Analysis of Development Teaching Materials for Interpersonal and Communication Courses based on a Team-Based Project Model using Podcast Media - Permana, Dede; Guslinda, Guslinda; Yohani, Adhisti Martha; Rahayuningtyas, Putri (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This qualitative descriptive study aims to determine the needs of students and lecturers for team-based, project-based teaching materials in interpersonal and communication skills courses. Data collection was obtained through observation, interviews and document study. The results of observations during the implementation of interpersonal and communication skills courses in obtaining an overview of students’ public communication experiences. Students are not used to it and seem passive when communicating in public. Students also have difficulty adapting their communication style to suit various interlocutors. The analysis of the questionnaires revealed that most did not have teaching materials for interpersonal communication skills courses and admitted that they needed them for courses in these subjects. Meanwhile, interview data supported by study documents revealed that lecturers and students need open materials packaged specifically for implementing interpersonal and communication skills courses. Teaching materials need to be presented in a structured manner and be able to create collaborative learning. Open materials can utilize digital media. Teaching materials are expected to improve students’ interpersonal and communication skills. Based on these findings, it can be concluded that it is necessary to develop teaching materials that are integrated with the team-based project model by utilizing digital media.